Penerapan Model Pembelajaran Kooperatif terhadap Hasil Belajar Matematika ditinjau dari Tingkat Motivasi - Ardianik; Aulia, Kiara Cindy; Setiawan, Windi (Universitas Nahdlatul Ulama Pasuruan, 2022)
The purpose of this study was to determine the differences in various cooperative learning models such as the Jigsaw type, the STAD type, and the GI type. This research is a quasi-experimental research. The sample consisted of three classes, namely class 7A subjected to treatment I, class 7B was subjected to treatment II, and class 7C to treatment III, sampling was carried out using cluster sampling technique. Data collection techniques using the method of tests and questionnaires. The data analysis technique used Kruskal Wallis non-parametric statistics. The results of data analysis resulted in 5 different hypotheses. The first hypothesis is the value of Asym Sig. 0.000 < 0.05, the second hypothesis obtained the value of Asym Sig. 0.000 < 0.05, the third hypothesis obtained the Asym Sig value. 0.280 is greater than 0.05, the fourth hypothesis is obtained by the Asym Sig value. 0.000 is smaller than 0.05 and the last hypothesis is the Asym Sig value. 0.006 < 0.05.